Antioxidant vitamin intake and mortality in three Central and Eastern European urban populations: the HAPIEE study - Stepaniak, Urszula; Micek, Agnieszka; Grosso, Giuseppe; Stefler, Denes; Topor-Madry, Roman; Kubinova, Ruzena; Malyutina, Sofia; Peasey, Anne; Pikhart, Hynek; Nikitin, Yuri; Bobak, Martin; Pająk, Andrzej (European journal of nutrition, 2016)
PURPOSE: The aim of the study was to assess the relationships between individual-level dietary intakes of antioxidant vitamins C, E and beta-carotene with all-cause and cause-specific mortality in three Central and Eastern European (CEE) populations. METHODS: Data from the Health, Alcohol and Psychosocial factors in Eastern Europe cohort study were used. At the baseline survey, between 2002 and 2005, 28,945 men and women aged 45-69 years were examined in Novosibirsk (Russia), Krakow (Poland) and seven Czech towns. Deaths in the cohorts were identified through mortality registers. Cox regression was used to estimate the association between vitamin consumption and all-cause, cardiovascular (CVD) disease and cancer mortality. RESULTS: In multivariable-adjusted analyses, there were no clear inverse associations between antioxidant vitamin intakes and mortality, although in some groups, several hazard ratios (HRs) were significant. For example, in men, compared with the lowest quintile of vitamin C intake, all-cause mortality in the third and fourth quintiles was lower by 28 % (HR 0.72; 95 % CI 0.61-0.85) and by 20 % (HR 0.80; 95 % CI 0.68-0.95), respectively. CVD mortality was lower by 35 % (HR 0.65; 95 % CI 0.50-0.84) and by 23 % (HR 0.77; 95 % CI 0.59-0.99) in third and fourth quintile of vitamin C intake, respectively. In women, the third and fourth quintiles of dietary intake of vitamin E were associated with reduced risk of all-cause death by 33 % (HR 0.67; 95 % CI 0.53-0.84) and by 23 % (HR 0.77; 95 % CI 0.61-0.97), respectively. Consumption of vitamin C, vitamin E and beta-carotene was not related to CVD mortality in women and to cancer mortality in either gender. CONCLUSION: This large prospective cohort study in CEE populations with low prevalence of vitamin supplementation did not find a strong, dose-response evidence for protective effects of antioxidant vitamin intake.
Keywords: Socioeconomic Factors; Russia; proporcionální rizikové modely; Vitamins; antioxidancia; Central and Eastern Europe; Male; Neoplasms; Risk Factors; následné studie; Mortality; Poland; Česká republika; kyselina askorbová; Urban Population; Proportional Hazards Models; příčina smrti; socioekonomické faktory; Aged; Prospective Studies; mužské pohlaví; senioři; Ascorbic Acid; průzkumy a dotazníky; potravní doplňky; Dietary Supplements; Follow-Up Studies; Czech Republic; Cardiovascular; vitaminy; kardiovaskulární nemoci; beta-karoten; beta Carotene; lidé; ženské pohlaví; Antioxidants; Humans; Antioxidant vitamin; rizikové faktory; Rusko; vitamin E; nádory; Cardiovascular Diseases; Vitamin E; Female; Surveys and Questionnaires; Polsko; lidé středního věku; Cause of Death; městské obyvatelstvo; Middle Aged; prospektivní studie